2001
DOI: 10.1023/a:1011265810471
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Compliant mechanisms are single-piece flexible structures that deliver the desired motion by undergoing elastic deformation as opposed to jointed rigid body motions of conventional mechanisms. Compliance in design leads to jointless, no-assembly ( Fig. 1), monolithic mechanical devices and is particularly suited for applications with small range of motions. The compliant windshield wiper shown in Fig. 1 illustrates this paradigm of noassembly. Conventional flexural mechanisms employ flexural joints that connec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 154 publications
(29 citation statements)
references
References 8 publications
0
29
0
Order By: Relevance
“…Issa et al embedded resistive sensing elements made of a conductive silicone elastomer into the connections of a compliant mechanism, and showed that it was possible to detect the presence of the object being held. Due to the simplicity of the structure, compliant mechanisms are also suitable for microgrippers …”
Section: Gripping By Actuationmentioning
confidence: 99%
“…Issa et al embedded resistive sensing elements made of a conductive silicone elastomer into the connections of a compliant mechanism, and showed that it was possible to detect the presence of the object being held. Due to the simplicity of the structure, compliant mechanisms are also suitable for microgrippers …”
Section: Gripping By Actuationmentioning
confidence: 99%
“…Other commonly used compliant elements such as small-length flexural pivots can be incorporated into the analysis by using the appropriate values for the PRB parameters in Eqs. (11) and (17).…”
Section: Discussionmentioning
confidence: 99%
“…When the deformation under study is limited to instantaneous or small values, the analysis can often be performed using matrix algebra and screw theory [3][4][5][6][7]. However, when large deformation analysis is necessary, the methods used include beam theory [8,9], finite element analysis (FEA) [10,11], and pseudo-rigid-body (PRB) models [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…Flexure-based compliant mechanisms generally refer to mechanical devices gaining some or all of their mobility through elastic deformation of flexible members [1], which by nature possess the benefits of monolithic structure and variable stiffness over their rigid-body counterparts, thereby reducing friction, backlash, wear, no need for lubrication and assembly. Owing to these uniqueness, compliant mechanisms have been widely applied, including constant-force generation [2], multistable switches [3], micro-electro mechanical systems (MEMS) [4], precision positioning stages and grippers [5][6][7], micro/nanomanipulations [8], fast servotools in precision machining [9], servovalves [10], energy harvesting [11], microvibration suppression [12], alignment of optics, robotic actuation [13], and so forth.…”
Section: Introductionmentioning
confidence: 99%